2021
DOI: 10.1038/s41598-021-90117-6
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive assessment of left atrial and ventricular remodeling in paroxysmal atrial fibrillation by the cardiovascular magnetic resonance myocardial extracellular volume fraction and feature tracking strain

Abstract: Atrial fibrillation (AF) is a progressive disease that starts with structural or functional changes in the left atrium and left ventricle, and evolves from paroxysmal toward sustained forms. Early detection of structural or functional changes in the left atrium and left ventricle in the paroxysmal stage could be useful for identifying a higher risk of progression to persistent AF and future cardio-cerebrovascular events. The aim of this study was to test the hypothesis that the feature tracking (FT) left atria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Our study may support the usage of LAEF and LAS r the concept of HFpEF staging by integration of LV and LA mechanics [ 6 ], and consistent with the knowledge of previously described HFpEF phenogroup 2 of TOPCAT (Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist) trial, of which pathophysiology is characterized by older age, marked LA enlargement, and high burden of diastolic dysfunction [ 36 ]. Moreover, LA strain assessment also predicts AF progression in HFpEF [ 34 ] and correlates with increased myocardial extracellular volume [ 37 ] which indicates accumulation of extracellular matrix in HFpEF [ 38 ]. Treatments that target cardiac fibrosis [ 39 ] and LA reverse remodeling [ 40 ] may have benefit in such population.…”
Section: Discussionmentioning
confidence: 99%
“…Our study may support the usage of LAEF and LAS r the concept of HFpEF staging by integration of LV and LA mechanics [ 6 ], and consistent with the knowledge of previously described HFpEF phenogroup 2 of TOPCAT (Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist) trial, of which pathophysiology is characterized by older age, marked LA enlargement, and high burden of diastolic dysfunction [ 36 ]. Moreover, LA strain assessment also predicts AF progression in HFpEF [ 34 ] and correlates with increased myocardial extracellular volume [ 37 ] which indicates accumulation of extracellular matrix in HFpEF [ 38 ]. Treatments that target cardiac fibrosis [ 39 ] and LA reverse remodeling [ 40 ] may have benefit in such population.…”
Section: Discussionmentioning
confidence: 99%
“…We found that impaired LA booster function could be considered to ascertain subjects harboring ALDH2 polymorphism with modest alcohol consumption and could be used to independently identify AF in these subjects. As an active and key modulator against the presence of impaired LV diastolic kinetics, the LA booster pump function emerged as a strong marker that can be used for identifying AF incidence [ 43 , 44 ]; however, the exact mechanisms and clinical significance of our findings warrant further research.…”
Section: Discussionmentioning
confidence: 99%
“…The CMR data acquisition and post processing have been described in a previous study at our hospital (17). MR images were acquired using a 1.5-T scanner (Ingenia; Philips Healthcare, Eindhoven, Netherlands) with retrospective electrocardiographic gating.…”
Section: Cardiac Magnetic Resonance and Lung Perfusion Single-photon ...mentioning
confidence: 99%